Accelerated carbonation: state-of-the art of the research in Brazil - Pauletti, Cristiane (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The study of the behaviour of concrete in relation to carbonation is undertaken mainly through accelerated tests that demand rigid control o the variables that intervene in the process, but that have low execution costs and short data collection duration. In Brazil, like in other countries, there has been a large number of research studies that have aimed to improve those tests. However, there is not yet a widely accepted procedure that offers guidelines for its execution. This article presents the state of art of the research that has been developed in Brazil, considering the need to gather efforts on the development of future studies and to establish standardized test procedures. It suggests that there is a need for in-depth studies on carbonation concerned with CO2 concentrations, time and type of curing, and seasoning procedures adopted. For modelling and predicting service life it is also important to investigate the sample size and the exposure time to CO2, as well as to identify correlations between natural and accelerated tests in order to establish acceleration factors. This relationship between the two types of test is very important for understanding the phenomenon and produce guidelines for future definitions of standards.